A content analysis of the book Principles of Biology - Alcala, Leticia R.
The study is an attempt to use content analysis as a means of obtaining a profile judgment on certain variables observable in the book Principles of Biology by Lilia M. Rabago. It aims to know if the book is readable, as indicated by the proportion of technical and non-technical science words in the book, and if the book is inquiry-oriented or authoritarian. It also determines the index of student involvement in sample sentences in the verbal presentation, figures, tables and diagrams, and activities.